2013
DOI: 10.1097/brs.0b013e3182a69b90
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin and Pregabalin in the Management of Postoperative Pain After Lumbar Spinal Surgery

Abstract: 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(81 citation statements)
references
References 18 publications
1
76
1
3
Order By: Relevance
“…Additionally, both gabapentinoids reduced the amount of opioid consumption versus placebo [33]. In a systematic review and meta-analysis of randomized controlled trials, Yu et al found that both gabapentin and pregabalin were efficacious in reducing postoperative pain and narcotic requirements after lumbar spinal surgery [34].…”
Section: Anticonvulsants/calcium Channel A2-d Ligandsmentioning
confidence: 99%
“…Additionally, both gabapentinoids reduced the amount of opioid consumption versus placebo [33]. In a systematic review and meta-analysis of randomized controlled trials, Yu et al found that both gabapentin and pregabalin were efficacious in reducing postoperative pain and narcotic requirements after lumbar spinal surgery [34].…”
Section: Anticonvulsants/calcium Channel A2-d Ligandsmentioning
confidence: 99%
“…Indeed, procedure-specific meta-analyses still suffer from considerable statistical heterogeneity. 108 Therefore, we could find little empirical basis for conducting such procedure-specific reviews for adjuvant analgesics. However, we accept that this finding contradicts both previous research and clinical intuition.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, preoperative administration of acetaminophen and gabapentin have been shown to decrease opioid requirements, improve functional outcome, and increase patient satisfaction postoperatively [16][17][18]. These drugs may also decrease preoperative anxiety, pruritus, and postoperative shivering [19].…”
Section: Non-opioid Analgesicsmentioning
confidence: 99%